The Development of Electrically Conductive Polycaprolactone Fumarate-Polypyrrole Composite Materials for Nerve Regeneration - Runge, M. Brett (2010)
Electrically conductive polymer composites composed of polycaprolactone fumarate and polypyrrole (PCLF-PPy) have been developed for nerve regeneration applications. Here we report the synthesis and characterization of PCLF-PPy and in vitro studies showing PCLF-PPy materials support both PC12 cell and dorsal root ganglia (DRG) neurite extension. PCLF-PPy composite materials were synthesized by polymerizing pyrrole in pre-formed PCLF scaffolds (M(n) 7,000 or 18,000 g mol(−1)) resulting in interpenetrating networks of PCLF-PPy. Chemical compositions and thermal properties were characterized by ATR-FTIR, XPS, DSC, and TGA. PCLF-PPy materials were synthesized with five different anions (naphthalene-2-sulfonic acid sodium salt (NSA), dodecylbenzenesulfonic acid sodium salt (DBSA), dioctyl sulfosuccinate sodium salt (DOSS), potassium iodide (I), and lysine) to investigate effects on electrical conductivity and to optimize chemical composition for cellular compatibility. PCLF-PPy materials have variable electrical conductivity up to 6 mS cm(−1) with bulk compositions ranging from 5 to 13.5 percent polypyrrole. AFM and SEM characterization show microstructures with a root mean squared (RMS) roughness of 1195 nm and nanostructures with RMS roughness of 8 nm. In vitro studies using PC12 cells and DRG show PCLF-PPy materials synthesized with NSA or DBSA support cell attachment, proliferation, neurite extension, and are promising materials for future studies involving electrical stimulation.